Link duration probability based cross-layer routing protocol for epoch-based movement - SUN Jie; GUO Wei (Tongxin xuebao)
The end to end transmission performance is very poor because of routing failure caused by node movement in MANET.To solve this problem,an algorithm for the link duration probability of epoch-based movement was proposed,and based on which a link duration probability based cross-layer routing protocol for epoch-based movement（LPCP） was proposed.LPCP cross-layer interacts with transport layer,and considered both the maximum path availability and the minimum hops of an end to end connection.Three complementary mechanisms:routing switch,save then forward,ack reconfirm were proposed to prevent routing failure and the transmission efficiency reduction.It is shown by computer simulation that LPCP results in a significant improvement of the packet loss caused by routing failure,and increase the throughput much more.